Wannier-function approach to electron states in superlattices under an electric field - Bruno-Alfonso, A. (Elsevier B.V., 2004)
Electron quasi-stationary states in a periodic semiconductor superlattice are calculated, as linear combinations of Wannier-Kohn functions, for different values of an electric field applied along the heterostructure. A comparison with an alternative approach, which is based on the localization of quasi-stationary states, is performed. (C) 2004 Elsevier Ltd. All rights reserved.
Keywords: superlattice; electric field; Wannier-Stark; Wannier-function